“Paediatricians brace thyself” – Healthcare provider perspectives on childhood and adolescent hypertension: A qualitative study - Yamini Autkar Pusdekar; Jagannath V. Dixit; Akanksha P. Dani (Journal of Family Medicine and Primary Care)
Context: Paediatric and adolescent hypertension is becoming a public health concern as it contributes to the development of cardiovascular diseases. However, the problem largely remains undiagnosed. This makes early detection and institution of appropriate preventive measures difficult. The existing diagnostic guidelines and management policies for paediatric hypertension are complex. They have individual specific cut-offs (based on age, gender and height), making their interpretation difficult. Aims: The present study aims to gain insights into paediatrician's perspectives on childhood hypertension. Settings and Design: Qualitative Studies using Key Informant Interviews (KIIs) were conducted with paediatricians to know about their perspectives on blood pressure assessment in children and adolescents, its barriers, their experience, practices and expectations for main streaming hypertensive screening in national health programmes. The interviews were audio recorded after taking their consent. Statistical Analysis Used: Grounded theory was used to analyse transcripts. Results: A total of 40 providers within the public and private health sector were invited to participate; 36 consented and completed the interviews. There was a perception of increased prevalence of paediatric hypertension. Several system, provider and patient-level barriers, like unavailability of paediatric-sized cuffs, and complicated guidelines for interpreting blood pressure, prevented screening and accurate diagnosis. Conclusions: Despite the lack of guidelines for screening, paediatricians still recommended lifestyle interventions. They expressed concerns about implementing standard guidelines for screening. They also expressed the need for a clinical assessment tool to assist in accurate diagnosis. They were willing to contribute to the development and implementation of training programme for health providers to overcome barriers to blood pressure measurement in children.